Solaṅkī kālanuṃ sāhitya = Literature of the Solanki period - Śāha, Nīlāñjanā Subodha, 1934- (Gujarāta Yunivarsiṭī prakāśana., 1977)
A study on Sanskrit, Prakrit, and old Gujarati literature written during the Solanki period in Gujarat (942-1304 A.D.)